Meta’s Pay-or-Okay Model: An analysis under EU Data Protection, Consumer and Competition Law - D'Amico, Alessia; Pelekis, Dionysios; Teixeira Santos, Cristiana; Duivenvoorde, Bram (Technology and Regulation, 2024)
Meta introduced its ‘pay-or-okay’ model to respond to heightened requirements as to the way it collects users’ personal data for targeted advertising. This model entails giving users two options: paying for a tracking-free service or giving consent to personal data processing including targeted ads. While this resulted from the Meta ruling, in which the CJEU set out the requirements for freely given consent, this solution has caused a new wave of criticism, questioning whether it complies with EU law. More specifically, it raises potential concerns under data protection, consumer law, competition law and the Digital Markets Act. This paper analyses what issues this conduct creates under these areas of EU law and assesses the overall legality of the pay-or-okay model.